Abnormal goblet cell glycoconjugates in rectal biopsies associated with an increased risk of neoplasia in patients with ulcerative colitis: early results of a prospective study. Issue 12 (December 1984) - Boland, C R; Lance, P; Levin, B; Riddell, R H; Kim, Y S
Abstract : A group of 18 patients with stable ulcerative colitis involving the entire colon for at least eight years was subjected to a biopsy of normal appearing rectal mucosa and followed prospectively over four years for the development of either dysplasia or cancer. Goblet cell glycoconjugate structure was examined in the rectal biopsies using fluorescein conjugated lectins. At the beginning of the study, 13 of the 18 patients had abnormalities of goblet cell mucin or cytoplasmic glycoconjugates in the rectal biopsies. Dysplasia subsequently developed in six and carcinoma in one of these patients. Among the five patients with normal lectin binding studies in the initial rectal biopsies, colonic dysplasia has subsequently developed in one. The abnormalities seen in the rectal goblet cells resembled in part those previously seen in immature and neoplastic colonic cells. The dysplastic tissues all contained the form of mucin which has been found in other neoplastic colonic tissues. This preliminary report after four years of prospective study suggests that abnormalities of glycoconjugate structure may be associated with, and may precede, neoplastic events in the setting of chronic ulcerative colitis.